Likelihood testing of seismicity‐based rate forecasts of induced earthquakes in Oklahoma and Kansas. Issue 10 (18th May 2016) - Moschetti, M. P.; Hoover, S. M.; Mueller, C. S.
Abstract: Likelihood testing of induced earthquakes in Oklahoma and Kansas has identified the parameters that optimize the forecasting ability of smoothed seismicity models and quantified the recent temporal stability of the spatial seismicity patterns. Use of the most recent 1 year period of earthquake data and use of 10–20 km smoothing distances produced the greatest likelihood. The likelihood that the locations of January–June 2015 earthquakes were consistent with optimized forecasts decayed with increasing elapsed time between the catalogs used for model development and testing. Likelihood tests with two additional sets of earthquakes from 2014 exhibit a strong sensitivity of the rate of decay to the smoothing distance. Marked reductions in likelihood are caused by the nonstationarity of the induced earthquake locations. Our results indicate a multiple‐fold benefit from smoothed seismicity models in developing short‐term earthquake rate forecasts for induced earthquakes in Oklahoma and Kansas, relative to the use of seismic source zones. Key Points: Optimized spatial distribution forecasts use epicenter locations from the previous year and kernel smoothing distances of 10–20 km Probability gains achieved from the forecasts of induced earthquake locations decay over the course of about 6–12 months This work was motivated by the development of a short‐term seismic hazard model that includes the effects of induced earthquakes